(untitled) - Givone, Donald D (Boston, MA, 2003)
This exciting first edition provides more depth than existing digital design books, using a traditional approach to the subject. Digital Principles and Design contains introductory material in digital principles with emphasis on logic design, as well as more advanced material. With the exception of the digital circuits appendix, it assumes no background on the part of the reader. The text can be used by readers in computer science, computer engineering and electrical engineering.
Keywords: Digital electronics